MICROSTRUCTURE AND HARDNESS ANALYSIS OF DYNAMIC PLASTIC DEFORMATION ON CR-MN AUSTENITIC STAINLESS STEEL USING REPETITIVE HAMMERING - Selindiana, Cherly
Austenitic stainless steels have the advantage of consisting of high ductility and good corrosion resistance. The cold working process can be done to increase the hardness and strength of the material. However, because a metastable austenite phase occur in that material, there is a phase change of ? austenite to ?’-martensite and ?-martensite, which will reduce the ductility and its corrosion resistance. The strengthening process with dynamic plastic deformation (DPD) can prevent the formation of martensitic phases through repeated impact at high strain rates. In this study, microstructures and hardness evaluation on Cr-Mn austenitic stainless steel were analyzed as a result of dynamic plastic deformation through repetitive hammering method. Repetitive hammering with strain rate of 6,2 s-1 on Cr-Mn austenitic stainless steels were carried out on 5 specimens with variations in impact of 50, 100, 150, 250, and 350 times and impact energy of 486 J/cm2, 2.207 J/cm2, 2.569 J/cm2, 6.070 J/cm2, dan 11.330 J/cm2. Microstructure, hardness and XRD (X ray diffraction) analysis were carried out on specimens before and after repetitive hammering. Metallography is carried out to observe the microstructure using an optical microscope. The hardness was tested through hard Rockwell A. XRD examination was carried out to identify the phases formed and indications of nano-twins. The repetitive hammering process up to 350 times has succeeded in increasing hardness from 53.5 HRA to 71.6 HRA. Increased hardness due to plastic deformation resulting from repetitive hammering accompanied by formation of slip bands, cross bands, wavy bands, and indication of nano-twin formation show the success of strengthening Cr-Mn austenitic stainless steel through dynamic plastic deformation processes.